Principles of a New Protocol for Prediction of Azole Resistance in Candida albicans Infections on the Basis of ERG11 Polymorphisms - Caban, Monika (Springer US, 2016)
In recent years, Candida albicans infections treatment has become a growing problem because, among others, pathogenic strains are capable to develop resistance to the administered drugs. The elaboration of rapid and accurate method of resistance assessment is an important goal of many studies. They aim to avoid inappropriate dosage or drug choice, which may be life threatening in case of severe candidiasis. Here we propose a new protocol to predict C. albicans infections. The resistance prediction is based on high-resolution melt (HRM) analysis of ERG11 gene, especially, at the particularly unstable regions. Two statistically significant nucleotide polymorphisms were detected among twenty-seven strains isolated from saliva, one of which was silent mutation (Glu266Asp, Leu480Leu). We propose also HRM analysis as a convenient, simple and inexpensive method of preliminary selection of C. albicans DNA samples that vary in ERG11 nucleotide sequence within presumed region. Taken together, our study provides firm basis for the development of fast, simple and reliable methodology for diagnosis of C. albicans infections.